2022
DOI: 10.1371/journal.pgph.0000416
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment strategies and lessons learned from a large genetic study of African Americans

Abstract: Genetic studies must enroll large numbers of participants to obtain adequate statistical power. Data are needed on how researchers can best use limited financial and practical resources to achieve these targets, especially in under-represented populations. This paper provides a retrospective analysis of the recruitment strategies for a large glaucoma genetics study in African Americans. The Primary Open-Angle African American Glaucoma Genetics study enrolled 10,192 African American subjects from the Philadelph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…All subjects were ≥35 years and self-identified as Black (African ancestry, Afro-Caribbean, or African American). University of Pennsylvania (UPenn)-certified clinical research coordinators identified subjects during clinical visits to the Scheie Eye Institute, Perelman Center for Advanced Medicine, Philadelphia VA Medical Center, and Mercy Fitzgerald Hospital, as well as two neighboring ophthalmology clinics in Philadelphia, Pennsylvania (Windell Murphy, MD; Temple University) [ 21 ]. Additionally, a multimedia marketing campaign was employed with trusted African-ancestry community leaders to disseminate information and build trust in the community [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…All subjects were ≥35 years and self-identified as Black (African ancestry, Afro-Caribbean, or African American). University of Pennsylvania (UPenn)-certified clinical research coordinators identified subjects during clinical visits to the Scheie Eye Institute, Perelman Center for Advanced Medicine, Philadelphia VA Medical Center, and Mercy Fitzgerald Hospital, as well as two neighboring ophthalmology clinics in Philadelphia, Pennsylvania (Windell Murphy, MD; Temple University) [ 21 ]. Additionally, a multimedia marketing campaign was employed with trusted African-ancestry community leaders to disseminate information and build trust in the community [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several large-scale endeavors are responding to these recommendations, including the development of multi-ethnic biobanks that can be used for genetics research purposes [103][104][105][106][107][108]110]. Given the sheer number of data points needed for wellpowered genetics studies, the cost-benefit in the case of large-scale biobank development is evident [147]. Funding is paramount in genetics research, and financial support for genetics studies in underrepresented populations illustrates the progress that can be made [61].…”
Section: Support For Diverse Genetics Studiesmentioning
confidence: 99%
“…Funding is paramount in genetics research, and financial support for genetics studies in underrepresented populations illustrates the progress that can be made [61]. Simultaneously, care and culturally appropriate methods should be implemented in the building of such databases to ensure harm is not perpetuated and that population-specific contexts and goals are honoured [146,147]. While the addition of underrepresented populations to GWASs and biobank studies progresses, novel strategies in the cardiogenetic analysis of multi-ethnic data sets already available should be utilized and developed to begin increasing health and genetic care equity for underrepresented populations [113,114,148].…”
Section: Support For Diverse Genetics Studiesmentioning
confidence: 99%